Electronic, Thermodynamic Stability, and Band Alignment Behavior of the CoVSi/NaCl Heterojunction. (1st November 2022) - Amiri, Maliheh; Boochani, Arash; Nia, Borhan Arghavani
Abstract : We report the band discontinuity of the CoVSi/NaCl heterointerface. First principle calculations based on density functional theory using GGA, GGA + U, and GGA + mbJ approximations were applied to study the structural, electronic, and band alignment properties. Structural and thermodynamic stability studies indicate that this semiconductor - dielectric heterojunction can be synthesized experimentally in thermodynamic equilibrium conditions. The valence and conduction band offset values (VBO and CBO) were 0.74 and 3.02 eV, respectively. Also, the effective electron affinity parameter ( χ e ) for both CoVSi and NaCl were calculated as ∼1.51 and ∼0.769 eV, respectively, using Anderson's law. The study of the electronic structure expresses the occurrence of half-metallic ferromagnetic behavior with a narrow band gap of about 0.09 eV. In this heterojunction, electrons and holes were confined to the CoVSi layers, and conduction band minimum and valence band minimum were replaced in the CoVSi layers. This restriction, applied to load carriers on one side of the interface, significantly increases the light-material interaction in light-emission programs. Therefore, this heterojunction can be recommended for light-emitting applications and thin atomic layer materials with quantum confinement of charge carriers.